Caracterizando horoesferas do espaço hiperbólico via curvatura média de ordem superior - Nascimento, Edson Rafael Braga do (2021)
In this work our main objective is to study the results presented in the article “Characterizing horospheres of the hyperbolic space via higher order mean curvatures” by Cícero P. Aquino, Halyson I. Baltazar and Henrique F. de Lima. In this article the authors presented characterization results of horospheres in hyperbolic space in the context of higher order mean curvature. So, to achieve this goal, we also present the r-th mean curvature, Newton’s transformations and the differentiable operator Lr.